2007
DOI: 10.1021/cg070522r
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Inclusion by the Anti-HIV Drug Nevirapine: X-Ray Structures and Thermal Decomposition of Representative Solvates

Abstract: The preparation, X-ray crystal structures, and thermal analyses of five solvates of the non-nucleoside reverse transcriptase inhibitor Nevirapine are reported. Thermogravimetric traces for the solvates indicated the following compositions (N ) nevirapine): N • (ethyl acetate) 0.5 (1), N • (dichloromethane) 0.5 (2), N • (toluene) 0.5 (3), N • (water) 0.5 (4), and N • (1,4-dioxane) 1.5 (5). Centrosymmetric, hydrogen-bonded nevirapine dimers occur in the crystals of 1-3 and in a previously characterized, unsolvat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 7 publications
4
35
0
Order By: Relevance
“…Comparison of these traces with those for the previously described solvates nevirapineÁ(ethyl acetate) 0.5 and nevirapineÁ(dichloromethane) 0.5 [2] enabled us to deduce a common isostructurality of the host lattice. Based on our previously reported crystallographic data, it was thus possible to deduce that the members of the present series of solvates, containing a homologous series of primary alcohols, crystallize in the triclinic space group P(-1) with predicted unit cell dimensions a *7.8 Å , b *8.4 Å , c *12.4 Å , a *86, b *88°, c *68°.…”
Section: Dsc and Pxrd Characterizationmentioning
confidence: 94%
See 2 more Smart Citations
“…Comparison of these traces with those for the previously described solvates nevirapineÁ(ethyl acetate) 0.5 and nevirapineÁ(dichloromethane) 0.5 [2] enabled us to deduce a common isostructurality of the host lattice. Based on our previously reported crystallographic data, it was thus possible to deduce that the members of the present series of solvates, containing a homologous series of primary alcohols, crystallize in the triclinic space group P(-1) with predicted unit cell dimensions a *7.8 Å , b *8.4 Å , c *12.4 Å , a *86, b *88°, c *68°.…”
Section: Dsc and Pxrd Characterizationmentioning
confidence: 94%
“…Based on our previously reported crystallographic data, it was thus possible to deduce that the members of the present series of solvates, containing a homologous series of primary alcohols, crystallize in the triclinic space group P(-1) with predicted unit cell dimensions a *7.8 Å , b *8.4 Å , c *12.4 Å , a *86, b *88°, c *68°. In addition, by analogy with the known structures [2], it was possible to deduce that the common features in solvates 2-7 are: (a) a practically invariant host (nevirapine) framework, composed of centrosymmetric, N-HÁÁÁO hydrogen-bonded dimers, and (b) a channel running parallel to the crystal b-axis which accommodates the solvent molecules. These predictions, based on isostructurality analogy, were confirmed by single crystal X-ray diffraction studies (see below) and led us to describe these solvates more accurately as a series of isostructural channel-inclusion compounds.…”
Section: Dsc and Pxrd Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The alternate solid forms may have improved solubility and dissolution properties. Nevirapine has been reported in three polymorphic forms (26,27) and as some solvates or hydrates (24,28,29). However, not much information is available on the thermal properties.…”
Section: Introductionmentioning
confidence: 99%
“…The authors have reported the crystal structure of two solvate forms of nevirapine, hemihydrate (NEV3) and hemiethylacetate (NEV4) (Figure 4). Caira et al have also reported five different solvates of nevirapine (Caira et al, 2008 Figure 5). However, in the toluene solvate containing a larger guest molecule, the host dimers are packed in a different mode, but the guest molecules are again situated in channels.…”
Section: Nevirapinementioning
confidence: 89%